New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part II. Genus Bradysiopsis Tuomikoski, 1960 - Mohrig, Werner; Kauschke, Ellen (Zootaxa, 2016)
The genus Bradysiopsis Tuomikoski is new for the sciarid fauna of North America. It includes 6 species. Four of them are new for science. These are Bradysiopsis postvittigera sp. n., Br. praevittata sp. n., Br. praevittigera sp. n. and Br. subvittigera sp. n.. Two species, Br. vittata (Meigen, 1830) and Br. vittigera (Zetterstedt, 1851), are distributed in the Holarctic but new for North America. In this paper species are described, illustrated by figures and a key for classification as well as distribution data are given.